Chronostratigraphic correlation of the volcanic 1.21 Ga Barby and Haiber Flats Formations in the Sinclair Supergroup of Namibia. (June 2021) - Harris, M.; Mapani, B.S.; Cornell, D.H.; Malobela, T.; Weber, B.; Kristoffersen, M.; Lehman Francko, K.; Hanson, R.
Abstract: This work investigates Mesoproterozoic volcanic rocks of the Haiber Flats, Barby, Welverdiend and Kairab Formations, and associated intrusive rocks in the Konkiep Terrane. Various correlations have been made in the past and recent dating work yields contrasting ages. U–Pb dating of zircons is applied in combination with Sm–Nd and Lu–Hf isotopes to determine the age, assess correlation and ascertain the much-debated tectonic setting. Ion probe U–Pb zircon dating yields ages of 1218 ± 5 Ma, 1212 ± 4 Ma and 1212 ± 5 Ma (all errors 2σ) for three samples of the Haiber Flats Formation and 1219 ± 13 Ma, 1215 ± 19 Ma for the Barby Formation. The ages obtained for the Barby Formation agree with the 1217 ± 2 Ma and 1214 ± 5 Ma ages reported from previous investigations. Rocks mapped as the supposedly older Kairab rhyolite and felsic tuff gave younger ages of 1220 ± 4 Ma and 1222 ± 10 Ma, respectively, which are coeval with the Barby and Haiber Flats Formations. Two Gorab Gabbro samples, previously mapped as Kairab Formation, yield ages of 1341 ± 8 Ma and 1336 ± 8 Ma. These older ages are within error of two Welverdiend Formation samples which gave ages of 1344 ± 6 Ma and 1337 ± 9 Ma, and the formation was previously dated in the type area at 1327 ± 10 Ma. These ages confirm the reassignment of rocks originally mapped as tholeiitic Barby Formation into the Welverdiend Formation, north of a newly identified stratigraphic hiatus corresponding to the geophysically defined Wêreldend Lineament. Sm–Nd and Lu–Hf isotopic signatures for the Barby, Haiber Flats and coeval Kairab samples indicate that they are co-magmatic and derived from partly depleted mantle contaminated by older crust. TDM model ages of these samples range from 2.5 to 1.5 Ga with a major 2.2 to 1.8 Ga group. This suggests that the older crustal component was Paleoproterozoic but included some Archean material. The Welverdiend Formation and Gorab Gabbros show similarity in age, Sm–Nd and Lu–Hf characteristics and were probably derived from partially depleted mantle, or from a well-homogenised mixture of depleted mantle and older crust. REE diagrams indicate enrichment in LREE (La–Gd) and a flat HREE pattern (Tb to Lu). On spidergrams, most samples are characterised by negative Nb–Ta anomalies and positive K and Pb anomalies which indicate a subduction-related setting (with positive Sr anomaly) or a reworked crustal origin. The similarity in ages, isotopic signatures and geochemistry confirms the correlation of the Barby and Haiber Flats Formation. Highlights: U–Pb zircon dating show that the Haiber Flats and Barby Formation are coeval. Welverdiend Formation is older, Kairab Formation is redundant. Sm–Nd and Lu–Hf data indicate depleted mantle source contaminated by older crust. Rocks formed in a magmatic arc setting during assembly of Namaqua Terranes.